2022
DOI: 10.1590/1518-8345.5778.3537
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and resilience in intensive care Nursing professionals in the face of COVID-19: A multicenter study

Abstract: Objective: to analyze the relationship between the Burnout dimensions and the work resilience of intensive care Nursing professionals in the COVID-19 pandemic in four hospitals from southern Brazil. Method: this is a multicenter and cross-sectional study, composed of 153 nurses and nursing technicians of the Intensive Care Units. Sociodemographic, health and work-related questions were collected, and the Maslach Burnout Inventory and Resilience at Work Scale 20 instruments were applied. The data were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(32 reference statements)
1
3
0
2
Order By: Relevance
“…The results of the current study indicated that higher levels of resilience were associated with lower levels of emotional exhaustion, depersonalization, and diminished personal accomplishment among nurses working in Thailand during the pandemic period. The findings largely confirm previous studies where higher resilience has been linked to lower emotional exhaustion, depersonalization, and reduced personal accomplishment among nurses working in public hospitals in Madrid, Spain [ 20 ], nurse managers in tertiary public hospitals in China [ 25 ], nurses and nursing students from a college and a state nursing association in Pennsylvania, USA [ 18 ], nurses in Brazil [ 42 ], and hospital staff in Australia [ 4 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the current study indicated that higher levels of resilience were associated with lower levels of emotional exhaustion, depersonalization, and diminished personal accomplishment among nurses working in Thailand during the pandemic period. The findings largely confirm previous studies where higher resilience has been linked to lower emotional exhaustion, depersonalization, and reduced personal accomplishment among nurses working in public hospitals in Madrid, Spain [ 20 ], nurse managers in tertiary public hospitals in China [ 25 ], nurses and nursing students from a college and a state nursing association in Pennsylvania, USA [ 18 ], nurses in Brazil [ 42 ], and hospital staff in Australia [ 4 ].…”
Section: Discussionsupporting
confidence: 87%
“…An individual demonstrating resilience actively endeavors to progress constructively, drawing upon the insights and knowledge gained from confronting adverse experiences. Indeed, several studies among healthcare workers and nurses during the pandemic have found associations between resilience and lower levels of burnout [ 4 , 20 , 25 , 42 ], intention to leave [ 29 , 40 ] and a higher level of work engagement [ 9 , 26 ]. However, these studies have been limited to the United States, Australia, China, Brazil, and Spain.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review concluded that health professionals reported having moderate to high psychological resilience levels, despite the threat caused by the unknown virus and its consequences for mental health (59) . Resilience is an important protective factor for nurses (60) , although few research studies have been found on the influence of controllable work-related variables on nurses' resilience, and the factors that contribute to high or low resilience levels are still unclear (61) .…”
Section: Discussionmentioning
confidence: 99%
“…Uma revisão sistemática concluiu que profissionais de saúde relataram ter níveis moderados a altos de resiliência psicológica, apesar da ameaça causada pelo vírus desconhecido e das suas consequências para a saúde mental (59) . A resiliência é um fator importante de proteção para os enfermeiros (60) , embora tenham sido encontradas poucas investigações abordando a influência de variáveis controláveis relacionadas ao trabalho, na resiliência do enfermeiro, e os fatores que contribuem para níveis de resiliência altos ou baixos ainda não sejam claros (61) . A pandemia encorajou inúmeras mudanças das formas tradicionais de ensino e pesquisa, principalmente a utilização de intervenções on-line, como o uso de aplicativos e videoconferências, com sucesso na melhora da compaixão e saúde mental dos usuários (62)(63) .…”
Section: Aspectos éTicosunclassified